New leafy vegetables from Andaman Islands - Singh, Shrawan; Singh, D R; Roy, S D (Indian Horticulture, 2019)
The scientific cultivation of recently added varieties of leafy vegetables gives an opportunity to harvest high yield of better quality in tropical islands which fetches higher market prices than traditionally grown crop. These varieties are more uniform and attractive for consumers which will improve consumer acceptance. Thus, growing of identified new leafy vegetables appears as a viable proposition to meet nutrition gap in rural areas. However, possibilities of these crops in kharif season in North India and both seasons in southern and coastal regions need to be established through research trials.